Optical enhancement and selenisation models of CuInSe2 films by substrate choosing processes. (June 2013) - Ji, X; Wang, L J; Teng, J Y; Mi, Y M; Zhang, C M
Abstract : In this research, substrate materials have been used for the production of the absorbed layer of salor cell–CuInSe2 films. The microstructures of CuInSe2 films have been studied through X-ray diffraction and scanning electron microscopy. Surface character and optical properties of CuInSe2 films have been investigated on the substrate materials [Si, Al, SnO2 doped F (SFO), Cu and steel]. The results show that CIS phase was changed from amorphous structure to single phase structure with the substrate changed from Si to Al, steel and Cu. It also found that only two-phase structures existed in the CIS films on SFO. Meanwhile, substrate processes were found to be a vital parameter in determining the selenisation mechanism and grain size of the CIS films. An inverse relation between the substrate materials and the optical properties of the CIS films was observed.